Efektifitas Organisasi Himpaudi Dalam Peningkatan Mutu Pendidikan Anak Usia Dini (PAUD) di Kota Bandar Lampung - Markuri, Popi; Yetri, Yetri; Fakhri, Jamal (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
This research aims to assess the extent of Himpaudi organization's effectiveness in improving the quality of Early Childhood Education (PAUD) in the city of Bandar Lampung. Using a qualitative approach, this study focuses on a narrative and case study approach. The primary data sources were obtained through interviews with Himpaudi leaders, management members, and relevant PAUD officials in the Bandar Lampung sub-district. Data collection techniques included observation, structured interviews, and document collection. The data analysis process involves data reduction, presentation, and drawing conclusions based on the gathered information. The research findings reveal that Himpaudi faces challenges in enhancing the quality of PAUD in Bandar Lampung. Despite external support, there are weaknesses in the organization's structure and implementation. Other challenges include ineffective coordination and varying levels of member participation. Although Himpaudi's policies and management are functioning well, there is a need for more internal evaluation and oversight. Furthermore, there are challenges in Himpaudi's PAUD development strategy, particularly concerning expansion, quality improvement, and deeper involvement of the community and partners.